Efficiency of the Hydroponic System as an Approach to Confirm the Solubilization of CaHPO4 by Microbial Strains Using Glycine max as a Model - Reis, Mateus Neri Oliveira; Bessa, Layara Alexandre; de Jesus, Andressa Pereira; Guimarães Silva, Fabiano; Moreira, Marialva Alvarenga; Vitorino, Luciana Cristina (Frontiers in Plant Science, 2021)
The sustainable development of agriculture can be stimulated by the great market availability of bio-inputs, including phosphate-solubilizing microbial strains. However, these strains are currently selected using imprecise and questionable solubilization methodologies in solid or liquid media. We hypothesized that the hydroponic system could be a more efficient methodology for selecting phosphate-solubilizing strains as plant growth promoters. This methodology was tested using the plant Glycine max as a model. The growth-promoting potential of the strains was compared with that of Biomaphos® commercial microbial mixture. Calcium phosphate (CaHPO4) solubilization results obtained using the hydroponic system were inconsistent with those observed in solid and liquid media; however, the tests in liquid medium demonstrated poor performances of Codinaeopsis sp. (328EF) and Hamigera insecticola (33EF) in reducing pH and solubilizing CaHPO4, which corroborates with the effects of biotic stress observed in G. max plants inoculated with these strains. Nevertheless, the hydroponic system allowed the characterization of Paenibacillus alvei (PA12), which is also efficient in solubilization in a liquid medium. The bacterium Lysinibacillus fusiformis (PA26) was the most effective in CaHPO4 solubilization owing to the higher phosphorus (P) absorption, growth promotion, and physiological performance observed in plants inoculated with this bacterium. The hydroponic method proved to be superior in selecting solubilizing strains, allowing the assessment of multiple patterns, such as nutritional level, growth, photosynthetic performance, and anatomical variation in plants, and even the detection of biotic stress responses to inoculation, obtaining strains with higher growth promotion potential than Biomaphos®. This study proposes a new approach to confirm the solubilizing activity of microorganisms previously selected in vitro and potentially intended for the bio-input market that are useful in P availability for important crops, such as soybeans.